ANALYSIS AND RESULTS OF TERRITORIAL INDICATORS OF INVESTMENT ACTIVITY IN UZBEKISTAN - Karimova Komila Daniyarovna (American Journals, 2023)
The article provides an in-depth analysis of regional indicators of investment activity in the country. Science-based proposals and recommendations have been developed to focus on important aspects of investment activity in the effective conduct of investment activities in the regions, to increase local investment activity, as well as to continuously develop the level of activity in regional investment policy.
Keywords: action strategy, investment policy, investment activity, investment fund, domestic and foreign investment, free economic zones, investment activity, securities.